Once daily high dose probiotic therapy (VSL#3) for maintaining remission in recurrent or refractory pouchitis. Issue 1 (18th December 2003) - Mimura, T; Rizzello, F; Helwig, U; Poggioli, G; Schreiber, S; Talbot, I C; Nicholls, R J; Gionchetti, P; Campieri, M; Kamm, M A
Abstract : Background: Ten to 15% of patients with pouchitis experience refractory or recurrent disease. The aim of this study was to evaluate the effectiveness of a single daily high dose probiotic preparation (VSL#3) in maintaining antibiotic induced remission, and quality of life (QOL), for one year in such patients. Methods: Patients with pouchitis at least twice in the previous year or requiring continuous antibiotics, associated with a pouchitis disease activity index (PDAI) ⩾7 (0 = perfect; 18 = worst), in whom remission was induced by four weeks of combined metronidazole and ciprofloxacin, were randomised to receive VSL#3 6 g or placebo once daily for one year or until relapse. Symptomatic, endoscopic, and histological evaluations were made before, and two and 12 months after randomisation or at the time of relapse. Remission was defined as a clinical PDAI ⩽2 and endoscopic PDAI ⩽1. Relapse was defined as an increased clinical PDAI score ⩾2 and increased endoscopic PDAI score ⩾3. QOL was assessed using the inflammatory bowel disease questionnaire (IBDQ). Results: Thirty six patients were randomised: 20 to VSL#3 and 16 to placebo. Remission was maintained at one year in 17 patients (85%) on VSL#3 and in one patient (6%) on placebo (p<0.0001). The IBDQ score remained high in the VSL#3 group (p = 0.3) but deteriorated in the placebo group (p = 0.0005). Conclusion: The once daily high dose probiotic VSL#3 is effective in maintaining antibiotic introduced remission for at least a year in patients with recurrent or refractory pouchitis. This is associated with a high level of quality of life.